COMPETENCIES OF PEDAGOGICAL WORKERS IN THE FIELD OF ELECTRONIC SELF-ASSESSMENT SYSTEMS FOR PROFESSIONAL ACTIVITY - Radkevych, Oleksandr (Professional Pedagogics, 2024)
Relevance. The importance of implementing electronic self-assessment systems for pedagogical staff’s professional activities is described. It is emphasized that contemporary educational reforms require objective and transparent assessment mechanisms. It is determined that the implementation of such systems enhances the quality of the educational process. The development of digital and analytical competencies in educators for effective use of these systems is highlighted as necessary. Objective: The article aims to substantiate the competencies of pedagogical workers in the field of electronic self-assessment systems for professional activity. Methods: Surveys were used to assess educators’ perception and application of electronic systems in professional activities; interviews aimed at gaining deeper insights into individual experiences with these systems; document/literature analysis covered curricula, methodological recommendations, reports, articles on professional tasks, and other documents related to educators’ professional activities; observations focused on how teachers use electronic assessment systems in their daily professional activities and its impact on their interactions with students. Results: The research indicates that the implementation of electronic self-assessment systems in the context of educational reforms is a positive step. It was found that these systems enhance objectivity, transparency, and efficiency of assessments, developing key competencies in educators: informational-digital, evaluative-analytical, innovative, and reflective. The significance of continuous learning to adapt to technological changes is noted. It was observed that educators actively utilize digital tools such as online learning, video conferencing, Google Forms, and Padlet. Artificial intelligence, although slowly introduced, holds significant potential for personalizing education. Conclusions: The study underscores the importance of electronic self-assessment systems for improving education quality. The development of key competencies in educators—informational-digital, evaluative-analytical, innovative, and reflective – is crucial for the effective use of these systems. These competencies enable objective assessment of learning outcomes, adaptation of educational strategies, and enhancement of assessment transparency, which positively impacts the quality of the educational process. Continuous professional development ensures educators’ ability to adapt to technological changes and implement new teaching approaches. Electronic systems encourage reflection and professional growth, enhancing educators’ proficiency and creating a modern, interactive educational environment suited to the demands of the digital era.